Association of ACE2 gene functional variants with gestational diabetes mellitus risk in a southern Chinese population - Huang, Gongchen; Liang, Qiulian; Wang, Yukun; Qin, Linyuan; Yang, Haili; Lin, Lin; Yu, Xiangyuan (Frontiers in Endocrinology, 2022)
Objective: To explore the relationship between angiotensin-converting enzyme 2 (ACE2) genetic variants and gestational diabetes mellitus (GDM) in a southern Chinese population. Methods: Potential functional variants (rs2106809, rs6632677, and rs2074192) of ACE2 were selected and genotyped in 566 GDM patients and 710 normal pregnancies in Guilin, China. Odds ratio (OR) and its corresponding 95% confidence interval (CI) was used to evaluate the association between genetic variant and GDM risk, and then the false positive report probability (FPRP), multifactor dimensional reduction (MDR) and bioinformatics tools were used to confirm the significant association in the study. Results: After adjusting for age and pre-pregnancy body mass index (pre-BMI), logistic regression analysis showed that ACE2 rs6632677 was significantly associated with a decreased risk of GDM (CC vs. GG: adjusted OR = 0.09, 95% CI: 0.01 – 0.71, P = 0.023; GC/CC vs. GG: adjusted OR = 0.68, 95% CI = 0.46 – 0.99, P = 0.048 and CC vs. GG/GC: adjusted OR = 0.09, 95% CI = 0.01 – 0.72, P = 0.024); while rs2074192 was associated with increased GDM risk (TT vs. CC/CT: adjusted OR = 1.38, 95% CI = 1.08 – 1.75, P = 0.009). Further, we found that rs6632677 interacted with SBP (Pinteraction = 0.043) and FPG (Pinteraction = 0.021), and rs2074192 interacted with HDL-c (Pinteraction = 0.029) and LDL-c (Pinteraction = 0.035) to influence the GDM risk of individual. In the multiple dimension reduction (MDR) analysis, the rs6632677 was the best one-locus model and the 3-loci model was the best interaction model to predict GDM risk. In addition, functional analysis confirmed that rs2074192 may regulate the splicing process of ACE2 gene. Conclusion: ACE2 gene variants are significantly associated with the risk of GDM via gene-gene and gene-environment combination. The rs2074192 C > T affects the splicing of ACE2 gene, which may be a potential mechanism leading to the changed susceptibility of individual female during pregnancy to GDM.